Air Conditioning System Analysis for Two Floors Electronic Industrial Building Size 40 X 25 X 10 Meters At PT. CI. In Jakarta - Srihanto, Srihanto; Widarmadi, Indra; Anam, Sahidul; Sinaga, Parman; Yulianto, Sigit (Universitas Ibn Khaldun Bogor, 2023)
Air fresheners or AC (Air Conditioning) systems are increasingly becoming a necessity for urban communities and the industrial world in Jakarta. AC functions to cool industrial rooms, offices and homes. The PT CI Electronic Industry Building, has not yet installed an air conditioning system so that the production room is not comfortable for its employees. The purpose of installing air conditioning in the industrial building is to increase employee comfort and productivity. In installing an air conditioning (AC) system in the industrial building, design data and cooling load analysis are required. Therefore it is necessary to study the design of industrial air conditioners at PT CI by calculating the cooling load, calculating the required electrical power in order to determine the size and type of air conditioner needed. The research methodology starts from determining industrial building data, such as what tools and machines are in the room, the area of the room and the room wall materials, then analyzing the cooling load, determining the power of the cooling machine and determining the cooling system used. From the results of the cooling load analysis in the Electronics Industry building at PT CI, the total load on floors 1 and 2 was 709 kW, or 201,6 TR, including sensible load: 705.83 kW and Latin load: 3.03 kW. The refrigerant used by the AC R 134a engine. The compressor power is 356 HP. Medium large COP 2.8. The cooling system chosen is the central air conditioning system.